Guatemala : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This 2013 Article IV Consultation highlights that key developments in Guatemala since the 2012 Article IV Consultation have been positive. As commodity prices stabilized and domestic demand pressures weakened, inflation fell sharply in 2012-closing at 3.4 percent by December. Although subsequently inflation rose somewhat-to 4.3 percent by May 2013, owing mainly to domestic prices-it still remained within the central bank's target range of 4.0n1 percent. The economic outlook is generally benign. Growth is expected to edge up to 3 1\2 percent in 2013 and 2014, reaching its potential rate, supported by ongoing buoyant domestic demand and healthy private-sector credit.